Sacredscapes and pilgrimage systems - Singh, Rana P.B. (ed.); Timothy, Dallen J. (Fwd.) (Gurugram Shubhi, 2021)
The twelve essays deal with current debate in pilgrimage studies and spirit of place that helps to understand the deeper relationship between human psyche and sacred environment, citing illustrations from different parts of the world, like Canada, China, India, Israel, Nepal, Pakistan, Romania, Spain, and Tibet, representing many religions, linking locality with universality and narrating the prospective features. These studies will pave the path of the newly emerging discipline of pilgrimage studies and heritage ecology.
Keywords: Pilgrims and pilgrimages